Breastfeeding Practices and Food Consumption of Socially Vulnerable Children - Natália A. Oliveira; Nathalia Pizato; Érika S. O. Patriota; Ariene S. do Carmo; Gabriela Buccini; Vivian S. S. Gonçalves (Foods)
Promoting child well-being and development requires a multidimensional approach, including the right to adequate food practices. Socially vulnerable children are more exposed to adverse experiences, such as inadequate food consumption due to poverty. In this context, home-visiting programs are an important strategy for nutritional and health care education to provide relevant guidelines. This study describes breastfeeding and food consumption of children aged 0 to 24 months assisted by the Happy Child Program (Programa Criança Feliz—PCF) and aimed to investigate their association with socioeconomic factors and adherence to the program. This is an observational study, with a cross-sectional design, carried out with children assisted by the PCF in the Federal District, Brazil. Multivariate analysis was performed to identify sociodemographic and income factors, and household visits characteristics associated with breastfeeding, dietary diversity, and the consumption of ultra-processed food. A total of 301 children were assessed, 51.16% of whom were female. In 58.99% of households, the reference person was the mother; 86.20% were unemployed, and 27.08% had a low education degree. About 62.65% of beneficiaries lived on up to USD 200.00 per month and the majority faced food insecurity. The child’s age, and the mother’s current work situation were independently associated with the current breastfeeding situation, especially higher among women who did not work (p = 0.015). The minimum dietary diversity among children over 6 months old was 62.21% and presented a positive association with adherence to the program (p = 0.005). On the other hand, the consumption of ultra-processed foods was 77.21% and was associated with a longer follow-up time within the program (p = 0.047). The associations observed revealed the need to integrate family food choices and nutritional education into public policies for early childhood.